2015
DOI: 10.1016/j.bbamem.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics methods to predict peptide locations in membranes: LAH4 as a stringent test case

Abstract: Determining the structure of membrane-active peptides inside lipid bilayers is essential to understand their mechanism of action. Molecular dynamics simulations can easily provide atomistic details, but need experimental validation. We assessed the reliability of self-assembling (or "minimum-bias") and potential of mean force (PMF) approaches, using all-atom (AA) and coarse-grained (CG) force-fields. The LAH4 peptide was selected as a stringent test case, since it is known to attain different orientations depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 69 publications
5
49
0
Order By: Relevance
“…These models are simplistic and, consequently, they have some limitations, and it is necessary to evaluate whether the selected model fits the purpose of the simulation [86]. However, these models have been used to evaluate drug-membrane interactions, such as volatile anaesthetics [89], antiparasitic drugs [90] and antimicrobial peptides [91][92][93][94][95][96][97][98]. Bereau and Kremer (2015) showed that MD simulations with coarse-grained models can lead to free energy profiles that are similar to those obtained by allatom simulations [99].…”
Section: Accepted Manuscriptmentioning
confidence: 92%
“…These models are simplistic and, consequently, they have some limitations, and it is necessary to evaluate whether the selected model fits the purpose of the simulation [86]. However, these models have been used to evaluate drug-membrane interactions, such as volatile anaesthetics [89], antiparasitic drugs [90] and antimicrobial peptides [91][92][93][94][95][96][97][98]. Bereau and Kremer (2015) showed that MD simulations with coarse-grained models can lead to free energy profiles that are similar to those obtained by allatom simulations [99].…”
Section: Accepted Manuscriptmentioning
confidence: 92%
“…Chemistry, University of Wisconsin Madison, Madison, WI, USA. Ongoing biophysical and structural investigations will be reported which aim to understand these activities at atomic resolution (5)(6)(7)(8). Apart from tracking membrane permeabilization caused by AMPs, we also observe the effect of AMPs on intracellular components such as the nucleoid and the ribosome.…”
Section: -Pos Board B207mentioning
confidence: 97%
“…A more efficient protocol was proposed in 2007 by Esteban- MartĂ­n and Salgado (2007), by which unordered lipids are allowed to self-organize in the presence of AMP. This strategy has recently led to successful results (Farrotti et al 2015;Khatami et al 2014;Wang et al 2013). …”
Section: Introductionmentioning
confidence: 94%